High intensity power training in middle-aged women with Charcot–Marie–Tooth disease: a case series. (2nd June 2021) - Hackett, Daniel; Roberts-Clarke, Daniel; Halaki, Mark; Burns, Joshua; Singh, Maria Fiatarone; Fornusek, Che
Abstract : Background/aims: High-intensity power training has been shown to be effective in improving muscular capabilities, functional performance and health-related quality of life in populations with physical impairments. However, the effectiveness of high-intensity power training in people with Charcot–Marie–Tooth disease remains uncertain. This case series investigated the effects of high-intensity power training on muscle performance, function and health-related quality of life in middle-aged women with Charcot-Marie-Tooth disease. Methods: Four women (age 51–58 years) with Charcot–Marie–Tooth disease type 1A participated in 8 weeks of supervised high-intensity power training. Results: All participants improved strength of the right hip abductors (46.7–109.7%) and left hip abductors (27.3–128.6%), maximal gait speed (2.3–9.1%), static balance (0.7–4.9%), tandem walk (−3.3 to −58.5%), and mental component scores on the Short Form 36 Health Status Survey (0.8–27.6%). Adherence to high-intensity power training was 100% and only one minor adverse event related to the intervention was reported. Conclusions: Although promising, larger controlled studies are indicated to confirm the safety and efficacy of high-intensity progressive resistance and power training in this cohort.